Polar bears past bedtime - Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 1998)
Their magic tree house takes Jack and Annie to the Arctic, where a polar bear leads them onto very thin ice.
"A Stepping Stone book."
Keywords: Polar bear; Bears; Magic; Tree houses